2024
DOI: 10.1021/acs.jced.3c00526
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Determination, Modeling, and Thermodynamic Analysis of 3-Aminophenol in Ten Monosolvents and Three Binary Mixed Solvents

Chenglou Wu,
Fumin Xue,
Xingzhu Wang
et al.

Abstract: The solubilities of 3-aminophenol in monosolvents (ethyl acetate, isopropyl acetate, n-butyl acetate, amyl acetate, 1,2-dichloroethane, trichloromethane, benzene, 1,4-dioxane, tetrahydrofuran, and acetonitrile) and binary solvent mixtures (1,4-dioxane + water, tetrahydrofuran + water, and acetonitrile + water) were determined by a static gravimetric method at temperatures ranging from 283.15 to 328.15 K under atmospheric pressure. The solubility of 3-aminophenol in all solvent systems is positively correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(52 reference statements)
0
0
0
Order By: Relevance
“…The thermodynamic phenomenon of cosolvency is unique and is a thermodynamically stable property, which can be reasonably applied in the pharmaceutical industries and health care products industries to increase miscibility. Generally, when the solubility of a compound in two mixed solvents is greater than its solubility in a single solvent, this phenomenon can be called cosolvency . In-depth research and the rational application of cosolvecny have profound implications and important significance in chemical engineering fields such as purification and crystallization. Cosolvency can also be used for the separation of chiral compound using ionic liquids . It also provides a new method for the development of high-performance materials. , Currently, an increasing number of cosolvency phenomena have been observed in many systems, which has attracted the widespread attention of researchers to explore its mechanism. ,, Some researchers suggest that the generation of the cosolvency may be caused by the similarity between solvent and solute molecules or the preferential solvation by the solvents. ,, Nevertheless, a considerable number of researchers have proposed that the cosolvency effect was induced by the changes in the spatial conformation of the compound molecules caused by the solvent composition changes, altering the intermolecular interactions between solute and solvent molecules. Moreover, in our previous studies, it was found that the cosolvency phenomenon of proline system is mainly attributed to the changes in the aggregate form of the l -proline molecules when varying the solvent composition, and the diverse form of aggregates can affect the intermolecular interactions between solute and solvent molecules with the changes in solution composition. Although some scholars have conducted research on the solubility difference of solutes in binary mixed solvents with similar structure and it has been found that the molecular structure of solvents has a significant impact on the solubility performance of solutes, the general mechanism of cosolvency has not been completely revealed and understood.…”
Section: Introductionmentioning
confidence: 99%
“…The thermodynamic phenomenon of cosolvency is unique and is a thermodynamically stable property, which can be reasonably applied in the pharmaceutical industries and health care products industries to increase miscibility. Generally, when the solubility of a compound in two mixed solvents is greater than its solubility in a single solvent, this phenomenon can be called cosolvency . In-depth research and the rational application of cosolvecny have profound implications and important significance in chemical engineering fields such as purification and crystallization. Cosolvency can also be used for the separation of chiral compound using ionic liquids . It also provides a new method for the development of high-performance materials. , Currently, an increasing number of cosolvency phenomena have been observed in many systems, which has attracted the widespread attention of researchers to explore its mechanism. ,, Some researchers suggest that the generation of the cosolvency may be caused by the similarity between solvent and solute molecules or the preferential solvation by the solvents. ,, Nevertheless, a considerable number of researchers have proposed that the cosolvency effect was induced by the changes in the spatial conformation of the compound molecules caused by the solvent composition changes, altering the intermolecular interactions between solute and solvent molecules. Moreover, in our previous studies, it was found that the cosolvency phenomenon of proline system is mainly attributed to the changes in the aggregate form of the l -proline molecules when varying the solvent composition, and the diverse form of aggregates can affect the intermolecular interactions between solute and solvent molecules with the changes in solution composition. Although some scholars have conducted research on the solubility difference of solutes in binary mixed solvents with similar structure and it has been found that the molecular structure of solvents has a significant impact on the solubility performance of solutes, the general mechanism of cosolvency has not been completely revealed and understood.…”
Section: Introductionmentioning
confidence: 99%